Effect of hybrid-fiber- reinforcement on the shear behavior of high-strength-concrete beams - Awad, Ahmed; Tawfik, Maged; Deifalla, A.; Ahmad, Mahmood; Sabri Sabri, Mohanad Muayad; El-said, Amr (Frontiers in Materials, 2023)
The shear behavior of concrete beams is higly affected by the implementation of better performance concrete. Hybrid fibers addition to concrete mixture has proven to improve the performance compared to just using single type of fiber. Thus, in this current study, the shear behavior of hybrid-fiber-reinforced-high-strength-concrete beams was investigated experimentally. In addition, the effect of the span-to-depth ratio and the transverse reinforcement ratio were examined. Results showed that, when 0.45% of the cement weight is replaced with polypropylene fiber and 7% of the cement weight is replaced with steel fibers, the shear strength of the beam was enhanced by 18% in comparison to the control beam. The Formation and progression of cracks were also better controlled. The behavior of hybrid-polypropylene-steel-fibers-high-strength-concrete beams was observed to be comparable to that of conventional concrete ones as the shear strength increased with the decrease in span to depth ratio or the increase in transverse reinforcing ratio. A non-linear numerical model was developed and validated using the experimental results. The shear capacities of beams were calculated using ACI, which was compared to experimental and numerical results. The ACI's calculations were remarkably conservative when compared with the experimental or numerical results. The coefficient of variance between the ACI and experimental shear capacity results was 4.8 %, while it was 9.2% between the ACI and numerical shear capacity results.